Considerações atuais da sialolitíase de ducto de glândula submandibular - Silva, Alan Roger Santos [UNESP]; Soares, Gláucia Resende; Soubhia, Ana Maria Pires [UNESP]; Miyahara, Glauco Issamu [UNESP] (My University, 2010)
The sialolithiasis is characterized by the formation of calcified structure called sialolith within the salivary ductal system. Although its etiology is unknown, it is believed that is from the deposition of calcium salts around an accumulation of organic leftovers in the lumen of the duct or be resulted by chronic sialadenitis and partial obstruction. In this study, the authors describe a case of a male patient, 46 years old, brown, who presented the complaint “pain under the tongue.” The presence of a hardened nodule located in the left sublingual fold was observed through intra-oral exam. Current considerations about treatment, clinical and radiographic characteristics were addressed in this work.

A sialolitíase é caracterizada pela formação de estrutura calcificada chamada sialolito no interior do sistema ductal salivar. Apesar de sua etiologia ser desconhecida, acredita-se que se origine da deposição de sais de cálcio ao redor de um acúmulo de restos orgânicos no lúmen do ducto, ou ainda ser desencadeada por sialoadenite crônica e obstrução parcial. Neste trabalho, os autores descrevem um caso de um paciente do sexo masculino, 46 anos de idade, cor parda, que apresentou como queixa “dor embaixo da língua”. Ao exame intra-oral foi observada a presença de um nódulo endurecido localizado na prega sublingual esquerda. Considerações atuais sobre características clínicas, radiográficas e tratamento foram abordadas neste trabalho.
Current considerations of sialolithiasis duct of submandibular gland
Keywords: Gland calculi; Salivary glands; Therapeutics; Cálculos das glândulas salivares; Glândulas salivares; Terapêutica